2004
DOI: 10.4315/0362-028x-67.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic and Proteolytic Activities of Aeromonas hydrophila and Aeromonas veronii Biovar sobria in Broth and Salmon Extract at Different Temperatures

Abstract: Expression of hemolytic and proteolytic activities throughout the growth cycle was investigated with two enterotoxic aeromonad strains assigned to the species Aeromonas hydrophila and Aeromonas veronii biovar sobria. Although growth kinetic data were dependent on strain, temperature, and substrate, maximum populations attained were higher than 9 log CFU/ml in aerated tryptone soya broth plus yeast extract (TSBYE) and salmon extract within the range 4 to 28 degrees C. For both strains in TSBYE, variable amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Similarly, Aeromonas hydrophila is considered an opportunistic fish pathogen and may be more aggressive in tropical environments, but certain strains are also regarded as human pathogens (Janda and Abbott 1998), and in fact, the strain is regarded as a zoonotic bacteria (an animal-infecting strain that also infects humans) (Gonzalez et al 2001;Lehane and Rawlin 2000). Virulence markers have been reported for both species of Aeromonas isolated in this study from freshwater fish and from a case of human diarrhea (Gonzalez-Serrano et al 2002), and hemolytic and proteolytic activities are reported from both strains (Gonzalez-Rodriguez et al 2004). Again, there is no evidence to suggest that the isolates in this study are human pathogens, although they were not tested for the presence of pathogenicity genes as a part of this study.…”
Section: Bacteriamentioning
confidence: 54%
“…Similarly, Aeromonas hydrophila is considered an opportunistic fish pathogen and may be more aggressive in tropical environments, but certain strains are also regarded as human pathogens (Janda and Abbott 1998), and in fact, the strain is regarded as a zoonotic bacteria (an animal-infecting strain that also infects humans) (Gonzalez et al 2001;Lehane and Rawlin 2000). Virulence markers have been reported for both species of Aeromonas isolated in this study from freshwater fish and from a case of human diarrhea (Gonzalez-Serrano et al 2002), and hemolytic and proteolytic activities are reported from both strains (Gonzalez-Rodriguez et al 2004). Again, there is no evidence to suggest that the isolates in this study are human pathogens, although they were not tested for the presence of pathogenicity genes as a part of this study.…”
Section: Bacteriamentioning
confidence: 54%